ANALISIS PENERAPAN AKUNTANSI PADA BISNIS PAKAIAN THRIFT - Lestari, Sari; Anggraini, Arianti Dwi; Caryadi (Cahaya Ilmu Bangsa, 2025)
This study aims to analyze the application of accounting in a second clothes business or thrift. We chose one of the thrift businesses located in Bekasi City as the object of this research. The thrift business, which involves the sale of second clothes at affordable prices, is increasingly popular in various circles of society because of its uniqueness. This study uses a qualitative research method with data collection through interviews and direct observation of the business owner. Primary data was obtained from direct interviews with business owners, while secondary data was obtained by the author from related literature. The results showed that this thrift business has been carrying out manual and simple recording of transactions, with transactions. Nevertheless, the business owner realizes the importance of financial recording, although it is done in a limited way due to a lack of understanding of accounting. The records include sales transactions and store expenses, which are classified into one-month periods. However, the business owner has never calculated the profit or loss from her business activities. Because business owners do not understand the recording of good financial statements in recording financial statements in accordance with applicable Financial Accounting Standards. Thus, the author provides recommendations regarding more effective accounting records for the thrift business.